CT imaging characteristics of nontuberculous mycobacteria lung disease, active tuberculosis and multi-drug resistant tuberculosis - Xu, Liang; Xu, Shuangmei (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: The differential diagnosis of nontuberculous mycobacteria (NTM) lung disease, active tuberculosis (ATB) and multi-drug resistant tuberculosis (MDR-TB) remains difficult. Objectives: To explore the CT imaging characteristics of NTM lung disease, ATB and MDR-TB for differential diagnosis. Methods: Patients with NTM lung disease (n=98), ATB (n=98) and MDR-TB (n=98) who were examined and treated from August 2015 to May 2019 were included. Their chest CT imaging results were retrospectively analyzed, and the imaging characteristics were compared. Results: The proportion of cases complicated with underlying lung disease, cough and hemoptysis was significantly higher in NTM group than those in ATB and MDR-TB groups (P